Financialisation of Commodity Markets: Evidence from India. (February 2022) - Abraham, Rose Mary K.
The known circumstances that favour financialisation of commodity markets which result in unidirectional co-movement of equity and commodity indices are either weak or non-existent in India. Yet, after 2015, there has been a greater correlation between equity and commodity markets even when decoupling is observed in global markets. Results from the rolling regression attest to the shift in response of commodity and equity indices to wholesale price inflation (WPI) and call rate after 2015, indicating that post 2015 co-movement could have been a result of inflation targeting regime. The linear regression as well as the Granger causality analysis based on vector autoregression (VAR) framework, which accounts for simultaneity, confirms that commodity markets are moving on its own supply-demand factors. The rolling regression also brings to light the disciplining effect of regulatory scrutiny and audit trail in the Indian commodity market around July 2013, when National Spot Exchange Ltd. (NSEL) payment crisis and commodity transaction taxes (CTT) occurred. JEL Classifications: G180, G28, C580, G1, G100. G130